Developing Characters of Rehabilitation Students through Islamic Religious Education - Nelson Nelson; Karliana Indrawari; Koriatul Sadea; Restu Abdiyantoro (STAI Hubbulwathan Duri, 2024)
This research aims to address the issue of drug abuse by exploring the influence of adolescent peers. The study suggests that exposure to drug use among peers can lead to addiction in children. It is important to note that the language used in this study is objective and avoids any biased or emotional language. Effective solutions are proposed through spiritual rehabilitation or Islamic Religious Education. The research recognizes the significance of addressing psychiatric disorders arising from drug consumption and aims to contribute to character development through the incorporation of Islamic education within rehabilitation centers. This research uses a qualitative approach with descriptive methods, informant determination techniques using SnowBall sampling, data collection techniques through observation, interviews and documentation. Data analysis techniques through data reduction, data presentation and verification. The character-building process at the Drug Rehabilitation Center is flexible and involves tailored materials that are aligned with individual client needs. The study utilises lecture methods and question-and-answer sessions to facilitate comprehension. Additionally, project-based learning models are adapted to suit the taught material. Evaluation takes place after the explanation, requiring clients to promptly articulate or reapply the knowledge gained. The importance of ongoing assessment by coaches and administrators is underscored by the implications. This will ensure that clients not only grasp the material but also internalize and exhibit the desired moral values. It is recommended that teaching strategies be refined to align with the goal of instilling positive character traits in clients.